A novel design of low-grade waste heat utilization for coal-fired power plants with sulfuric acid recovery. (1st January 2021) - Ouyang, Tiancheng; Xu, Jisong; Su, Zixiang; Zhao, Zhongkai; Huang, Guicong; Mo, Chunlan
Graphical abstract: Highlights: A design of waste heat deep utilization with sulfuric acid recovery is proposed. Sulfur oxides in flue gas is converted into sulfuric acid as a by-product. Zeotropic mixture is employed as working fluid of organic Rankine cycle. A highly simplified absorption refrigeration model is proposed. A 14.43 MW improvement of equivalent net power output is realized. Abstract: Nowadays, serious resource shortages and environmental pollution remain puzzle for sustainable development of mankind. Energy conservation and emission reductions are inevitable historical trends, it must be reflected in idea and implemented in behaviour. Coal-fired power plants account for a great portion of energy supply, resource consumption and pollutant emissions in the same time, so it's an essential field to implement the energy conservation and emission reduction. To recover the low-grade waste heat of flue gas, a novel design that couples organic Rankine cycle and absorption refrigeration system with sulfuric acid recovery is proposed and applied in a 1000 MW coal-fired power plant. Sulfur dioxide in the flue gas is oxidized to sulfur trioxide when flows through catalyst beds, then the sulfur trioxide is condensed to sulfuric acid in a special heat exchanger. A binary zeotropic mixture with mass ratio of 0.303:0.697 is adopted for organic Rankine cycle. After a degree-of-freedom analysis, eight independent variables are chosen as design variables to simplify the numerical model of absorption refrigeration system. Results show that the combined system can achieve a net power output of 8055 kW and a refrigeration capacity of 25493 kW. Meanwhile, a sulfuric acid production rate of 2123 kg/h can be realized ideally. This waste heat recovery system enhances the thermal efficiency of power plant case unit for 0.64% and the capital investment can be recovered within 5 years.